Poetika predmetnega v pesmih Jurija Vodovnika - Sitar, Jelena (Etnolog. Nova vrsta (Ljubljana), 2002)
We are constantly surrounded by objects which define our work and activities, and these objects often determine us more than we may notice or want to admit. When Vodovnik refers to common objects in his poems, he also refers to the people who use them. Describing the poetical aspect of an object, he also describes the poet in its owner. But when do we notice poetry or the poet in our fellow man. Only when we watch them lovingly, because that is the only view which transforms someone from an ordinary person into someone special. ToVodovnik the people of Pohorje - each and everyone of them which appears in his songs - were special people. This article attempts to describe some characteristic objects (requisites) which appear in Vodovnik's songs and whichtake on a poetic dimension because of the changed function, given to themby the poet Vodovnik.
Keywords: Vodovnik, Jurij, 1791-1858; predmeti; rekviziti; ljudski pesniki; Slovenia; Slovenija